Antimicrobial Defensin and DNA Traps in Manila Clam Ruditapes philippinarum: Implications for Their Roles in Immune Responses - Han, Yijing; Hu, Gege; Chen, Yuying; Chen, Lizhu; Yu, Daode; Zhang, Qianqian; Yang, Dinglong (Frontiers in Marine Science, 2021)
Although defensins have been isolated from a variety of metazoan, their role in cellular immunity has not been answered. In the study, we found that the hemocytes of the Manila clams Ruditapes philippinarum release defensin (designated as Rpdef3) in response to Vibrio parahaemolyticus challenge. The antimicrobial Rpdef3 was proved to be involved in the extracellular traps (ETs) that hemocytes released in response to Vibrio challenge. Scanning electron microscopy (SEM) observation proved the patterns how ETs eliminate invading bacteria. Furthermore, Rpdef3 involved in ETs had broad-spectrum antimicrobial effect on both Gram-negative bacteria and Gram-positive bacteria. ELISA assay revealed that Rpdef3 could bind lipopolysaccharides and peptidoglycan in a dose-dependent manner. As concerned to the antibacterial mechanisms, Rpdef3 can cause bacterial membrane permeabilization, leading to cell death. As a result, Rpdef3 might contribute to the trap and the elimination of invading Vibrio in clam ETs. Taken together, our study suggest that the formation of ETs is a defense mechanism triggered by bacterial stimulation, coupled with antibacterial defensin.